Grounding the prophet Muhammad eating manners: prophetic food as a local food literacy movement in elementary schools - Nuraly Masum Aprily; Nana Supriatna; Mubiar Agustin; Ernawulan Syaodih (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The low level of local food literacy among elementary school students, influenced by globalization and the dominance of instant food consumption, requires a more holistic educational approach. This article aims to formulate the conceptual framework of Prophetic Food as a literacy model grounded in the eating manners of Prophet Muhammad. A systematic literature review was conducted, screening 173 articles and narrowing them to 15 relevant studies using explicit inclusion and exclusion criteria. The analysis revealed three major themes: (1) the importance of school-based nutrition interventions in shaping healthy eating behaviors; (2) the increasing emphasis on halalan thoyyiban principles in food consumption; and (3) the relevance of local food systems for sustainability and cultural identity. Integrating the Prophet’s eating etiquette—simplicity, cleanliness, moderation, and communal sharing—this study proposes Prophetic Food as a framework built on five prophetic values: al-‘adl (justice), al-thohārah (cleanliness), qona’ah (moderation), al-karīm (generosity), and al-akhlaq al-karīmah (noble character). The findings conclude that Prophetic Food expands food literacy beyond nutrition toward ethical, spiritual, and sustainability-oriented education. Practical implications include project-based school activities, such as communal meals following prophetic traditions, and policy recommendations for integrating prophetic food literacy into the national curriculum.